Bentuk Pemertahanan Bahasa Jawa pada Interaksi Mahasiswa Fakultas Ilmu Budaya Universitas Brawijaya - Yolla, Eksanti; Vega Ari Prihartono; Nisrina Adnin Naqiyya; Aulia Latifah; Muhammad Rakha Badrudduja (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2024)
This research was conducted to examine the maintenance of the Javanese language with a focus on the forms and factors causing the maintenance of the language in the interactions of FCS UB students. The method in this research uses a qualitative descriptive method with the aim of describing the forms and factors of Javanese language defense in FCS UB student interactions. The research techniques used were field observation and interviews. Which is then complemented by Milles and Huberman's interactive analysis techniques, namely data reduction, presenting data, and drawing conclusions. The results of this research are (1) various forms of Javanese language maintenance, (2) supporting and inhibiting factors for Javanese language maintenance, namely the family environment and loyalty to Javanese as a mother tongue. Keywords: maintenance, language, javanese